Violation of the Cooperative Principle in the Mata Najwa Talk Show, Episode “3 Bacapres Bicara Gagasan” - Hariyanto, Prima; Suyuti, Muhammad Wildan; Hermawan, Nuri (BRIN Publishing (Penerbit BRIN), 2025)
The Presidential Election in Indonesia has always been a major event that gives rise to various aspects of communication. The Mata Najwa talk show edition “3 Presidential Candidates Discuss Ideas” received significant attention from the public and observers. This study aims to explain the forms of violations, the pragmatic functions of the violations, and the factors influencing the occurrence of violations of the cooperative principle in the Mata Najwa on Stage Yogyakarta edition “3 Presidential Candidates Discuss Ideas.” This research is a descriptive qualitative study. Data analysis employed a pragmatic equivalent approach. Based on the percentage, Anies Baswedan most frequently adhered to the cooperative principle, namely 29 times (72.50%), whereas Prabowo Subianto most frequently violated the cooperative principle, namely 15 times (38.46%). The pragmatic functions identified were assertive, directive, and expressive. The violations of the cooperative principle were in the form of violations of the maxims of quantity, quality, relevance, and manner. The factors influencing the occurrence of violations of the cooperative principle were sustaining communication, modesty, providing additional information, concealing messages/contradictions/predictions, covering up intentions, and preserving reputation. These findings contribute to the advancement of political discourse research by revealing how presidential candidates strategically employ conversational violations to achieve specific communicative goals, offering practical insights for understanding political communication strategies and their effects on public perception during electoral processes.